The Indians. - Time-Life Books; Capps, Benjamin, 1922- (New York, Time-Life Books, 1973)
Lavishly illustrated account of the lives, religion, customs, sports, homes, horses and history of the Indian tribes of the American West.
Bibliography: p. 236-237.
Young Adult
Keywords: Indians of North America -- West (U.S.); Indians of North America